Influence of Curing Temperature on Mechanical Properties of Woven Jute Reinforced Polyester Composite - Mustafa, Z.; Idrus, N.H.; Sheikh Md. Fadzullah, S.H.; Hadzley, A.B.; Shamsudin, Z.; Mohamad Razali, N.S.A.; Omar, N.I. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The aim of this work is to evaluate the influence of curing temperature onto the mechanical properties of woven jute/polyester composite using warm compression moulding. 40 vol.% woven jute fibres were compressed moulded at a pressure of 2.0 MPa, holding time of 900s by varying the fabrication temperature in three levels which are 150°C, 170°C and 180 °C. The mechanical and thermal properties were characterized using flexural and impact testing, DSC and TGA. Optimum mechanical properties are achieved at moulding temperature of 170°C. The flexural strength and flexural modulus at the optimised moulding temperature are 37.20 MPa and 0.84 GPa respectively, while their impact strength is 19.38 kJm-2. Morphological examination revealed that the composite failed in brittle manner and due to fibre pull-out indicating of weak interface.